From Acceptance Snapshots to the Social Acceptability Process: Structuring Knowledge on Attitudes Towards Water Reuse - Al-Saidi, Mohammad (Frontiers in Environmental Science, 2021)
Water reuse is considered a technologically viable option to meet the increasing demands of the domestic, industrial and agricultural sectors. Alongside challenges such as environmental health, infrastructure and regulations, water reuse is often hindered by lack of acceptance and dismissive attitudes. This paper seeks to structure knowledge about acceptance of water use. It provides a systematic look at the overall reuse challenges and social attitudes towards water reuse considering the three integrative elements of water reuse, namely the water source, the technology, and the end use. It first maps the challenges and common insights that constitute the enigma of water reuse acceptance. Later, it conceptualizes acceptance as a social process consisting of the interdependent components of public perception, politicization, individual acceptance, and use adaptation. Using this conceptual framework, solutions to increasing water acceptance stemming from different bodies of acceptance studies are reviewed. The paper reiterates the need for a nuanced view on water reuse acceptance that incorporates spatio-temporal considerations as well as knowledge from different disciplines.